The physiology and psychology of negative splits: insights into optimal marathon pacing strategies - Grivas, Gerasimos V. (Frontiers in Physiology, 2025)
Pacing strategy plays a critical role in marathon performance, influencing both physiological stress and race outcomes. Among the available pacing approaches, the negative split running the second half faster than the first has emerged as a potentially optimal strategy for endurance athletes. This mini-review explores the physiological mechanisms and psychological factors underpinning the effectiveness of negative splits in marathon running. Key advantages include improved energy conservation and glycogen sparing, enhanced thermoregulation, and reduced cardiovascular drift. These benefits contribute to delayed fatigue and greater efficiency in the latter stages of the race. Training modalities such as progressive long runs and fast-finish workouts, along with psychological techniques like goal setting and visualization, are discussed as tools to help runners implement negative split strategies. The article also examines the limitations and applicability of negative splits among elite and recreational runners, highlighting the need for individualized approaches based on fitness level, environmental conditions, and race profile. In conclusion, while not universally applicable, negative splits represent a scientifically grounded pacing method that may optimize performance in marathon running across a range of athlete populations.